Improving students' mastery on automotive electrical system using automotive electrical multimedia - Dwi Widjanarko; Herminarto Sofyan; Herman Dwi Surjono (Universitas Negeri Yogyakarta, 2016)
This research was conducted to study the improvement of students' understanding of automotive electrical system by applying automotive electrical multimedia. The multimedia was developed and validated by automotive and multimedia experts before being applied in teaching and learning processes. The research design was a single group pretest-posttest design with three field testing. The results showed that in the preliminary field testing, the students' understanding increased by 32.55%; in the main field testing, the understanding was up to 64.89%; and in the operational field testing, the understanding became 77.36%. This indicates that automotive multimedia could increase the students' understanding of automotive electrical system significantly.